2012
DOI: 10.1038/bmt.2012.253
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the development of atrial fibrillation and atrial flutter (AF/AFL) following autologous hematopoietic SCT (auto-HSCT)

Abstract: The use of autologous hematopoietic SCT (auto-HSCT) has expanded to include older patients. Increasing age is a well-appreciated risk factor for the development of atrial fibrillation and/or atrial flutter (AF/AFL) in the general population. As more elderly patients undergo auto-HSCT, the risk of developing AF/AFL post transplant may also increase. However, few data evaluating other risk factors for the development of AF/AFL following auto-HSCT exist. Therefore, we performed a retrospective study to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…To date, studies examining AF after HCT have been limited to patients undergoing autologous HCT, [32][33][34][35][36][37][38] representing an older population with greater comorbidities and a higher proportion of pre-HCT cardiotoxic (eg, chest radiation and anthracyclines) exposures, compared with patients undergoing allogeneic HCT. To our knowledge, our study is the first to describe the incidence and risk factors for AF in a contemporary cohort of allogeneic patients, allowing us to capture evolving HCT practices (eg, expanding donor stemcell source, use of nonmyeloablative conditioning, increasingly older age at HCT, and expanded indications for HCT).…”
Section: Discussionmentioning
confidence: 99%
“…To date, studies examining AF after HCT have been limited to patients undergoing autologous HCT, [32][33][34][35][36][37][38] representing an older population with greater comorbidities and a higher proportion of pre-HCT cardiotoxic (eg, chest radiation and anthracyclines) exposures, compared with patients undergoing allogeneic HCT. To our knowledge, our study is the first to describe the incidence and risk factors for AF in a contemporary cohort of allogeneic patients, allowing us to capture evolving HCT practices (eg, expanding donor stemcell source, use of nonmyeloablative conditioning, increasingly older age at HCT, and expanded indications for HCT).…”
Section: Discussionmentioning
confidence: 99%
“…31 articles were additionally excluded from full‐length review as they did not report the arrhythmia incidence or mortality risk/rate associated with arrhythmias in HSCT patients, and 23 articles were excluded because they were not observational studies. Ultimately, 13 cohort studies consisting of 10 587 HSCT patients were enrolled . The literature retrieval, review, and selection process are demonstrated in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Ultimately, 13 cohort studies consisting of 10 587 HSCT patients were enrolled. 1,3,7,[17][18][19][20][21][22][23][24][25][26] The literature retrieval, review, and selection process are demonstrated in Figure 1. The characteristics of the included studies are presented in Table 1.…”
Section: Re Sultmentioning
confidence: 99%
“…These patients showed a higher average heart rate ( P < 0.00010) and lower parasympathetic control ( P < 0.001) than the healthy group. [ 25 ] Steuter et al [ 26 ] retrospectively studied 516 patients who received auto-HCT and found that a history of arrhythmia was a risk factor for developing AF/AFL following HCT (odds ratio: 9.33, P < 0.001). However, the clinical impact of post-HCT arrhythmia needs to be further elucidated.…”
Section: Discussionmentioning
confidence: 99%